Heat assisted magnetic recording (HAMR) head design and simulation - Chaw, Li Huey (2014)
The storage capacity of hard disk drives (HDD) has extremely increased over the last decade. However, the rate of increase has reached a bottle-neck as the technology approaches a limit known as the superparamagnetic limit. Heat assisted magnetic recording (HAMR) is a promising approach for allowing increases in storage capability of HDD. HAMR was seen to be the solution for the bottle-neck faced by previous used recording methods. HAMR employs the use of a laser to momentarily heat the recording area of the medium to reduce the coercivity below the applied writing field. An optic delivery system is wisely designed to direct the laser beam into the recording medium and to prevent the heat loss from the laser in the read/write head. In this report, the author studied the thermal effect on the read/write head components and slider’s flying ability above the surface of the disk. ANSYS software is used to create a waveguide in the read/write head and thermal simulation is carried out to study the thermal protrusion and temperature distribution at the air bearing surface (ABS).